Welcoming Chinese investors in Indonesia: improving the competency of professional Indonesian-Mandarin translator. (March 2018) - Ying, Y; Mursitama, T N; Theresia,; Mariana,
Abstract: The study discusses the importance of improving the competency of Indonesian-Mandarin translators to increase economic relations between Indonesia and China. As China's investment in Indonesia expands in various industry sectors, the need for qualified translators escalates. However, the situation described that Indonesia lacks competent and qualified translators in Mandarin. The study adopts the qualitative approach. Technically, the study utilizes a variety of secondary data consisting of documents, books, publications, and website to collect data based on the needs of qualified translators and how to improve their competency. In addition, primary data collection involves industry and translation service providers, from high schools, vocational schools, colleges, and Chinese language courses through interviews. In this respect, the study contributes to the development of the Mandarin Chinese translator competency through professional translator training programs. The competencies developed include Mandarin language skills in a variety of contexts or themes such as business, industry, accounting, taxation, law, and socio-political issues. The findings of this research indicate the significance to complement the lack of knowledge and skills that are not acquired during the college. Importantly, the authors propose a professional interpreter training model to meet the demand of Chinese investors in Indonesia eventually.